Mortgage borrowing limits and house prices: Evidence from a policy change in Ireland - Brian E. Higgins (European Central Bank (ECB), 2024)
This paper studies how mortgage borrowers and house prices react to a tightening of mortgage limits following a policy change in Ireland in 2015. The policy introduced limits to the loan-to-income and loan-to-value ratios of new mortgages issued. In response to a tightening borrowing constraint, borrowers can choose to purchase a cheaper house or to reduce the leverage (LTV) of the mortgage. Using a difference-in-difference methodology, I find that groups of (poorer) borrowers, who were more likely to be above the loan-to-income threshold before the policy, responded primarily by buying cheaper houses after the policy change. On the other hand, groups of (richer) borrowers, who were more likely to be above the loan-to-value threshold, responded primarily by reducing the LTV of the mortgage. Borrowers who purchase cheaper houses could be buying smaller houses or the same size houses at a lower equilibrium price. To test for changes in equilibrium prices, I compare prices across postcodes and find that houses prices fell after the policy change in postcodes where a higher fraction of borrowers were above the loan-to-income threshold before the policy.
Keywords: G21; E21; E44; E58; R21; R30; 330; Macroprudential Regulation; Residential Housing Markets; House Prices; Household Leverage